2018
DOI: 10.1021/acs.est.8b05079
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Volatile Chemicals in Soil: Separating Volatilization and Degradation in an Improved Test Setup (OECD 307)

Abstract: During environmental risk assessments of chemicals, higher-tier biodegradation tests in soil, sediment, and surface-water systems are required using OECD standards 307, 308, and 309 guidelines, respectively. These guidelines are not suitable for testing highly volatile chemicals, and a biometer closed-incubation setup is recommended for testing slightly volatile chemicals. In this setup, the degradation kinetics of highly volatile chemicals can largely be influenced by volatilization. Additionally, guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In other non-standard studies where phenanthrene degradation has been measured in freshly spiked soils, halflives are generally in agreement with Shrestha et al [32] (Additional file 1: Table S1). In total, thirteen such studies were found in the literature, with phenanthrene being dosed to soils using varying approaches, including direct addition or solvent spiking of phenanthrene individually, as a composed PAH mixture, or as a constituent of materials such as crude oil [77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Experimental Data For the Soil Compartmentsupporting
confidence: 88%
See 2 more Smart Citations
“…In other non-standard studies where phenanthrene degradation has been measured in freshly spiked soils, halflives are generally in agreement with Shrestha et al [32] (Additional file 1: Table S1). In total, thirteen such studies were found in the literature, with phenanthrene being dosed to soils using varying approaches, including direct addition or solvent spiking of phenanthrene individually, as a composed PAH mixture, or as a constituent of materials such as crude oil [77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Experimental Data For the Soil Compartmentsupporting
confidence: 88%
“…Current European Chemicals Agency (ECHA) guidance places heavy emphasis on Organisation of Economic Co-operation and Development (OECD) guideline biodegradation tests. However, even with these standard tests, technical challenges remain that introduce variability and reliability issues, particularly where substance properties require modification to the standard test setups [28,[29][30][31][32].…”
Section: Difficulties In Persistence Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…"difficult to test chemicals") such as many petroleum hydrocarbons, which then necessitate signicant methodological adjustments. [4][5][6][7] While such adjustments should improve the technical and scientic quality of the tests and their degradation results, they can also lead to regulatory rejection of data. A very recent example of this is the persistency assessment of three ringed alkylated PAHs, where all 18 different biodegradation data sets identied were rejected and this hydrocarbon group was then assessed to be persistent without using the experimental degradation data.…”
Section: Introductionmentioning
confidence: 99%
“…The next presentation, based on research undertaken by the Fraunhofer IME for both Concawe and Cefic, identified the limitations and potential enhancements of the OECD 307 and OECD 309 tests. Some of the issues and recommendations for improvement for these tests have subsequently been published (Shrestha et al, 2019(Shrestha et al, , 2020. For example, both tests are considered to be poorly suited for the assessment of volatile substances.…”
Section: Session 3: Interpretation Of Simulation Testsmentioning
confidence: 99%